Does pre-operative embolization of a replaced right hepatic artery before pancreaticoduodenectomy for pancreatic adenocarcinoma affect postoperative morbidity and R0 resection? A bi-centric French cohort study. Issue 11 (November 2021) - Marichez, Arthur; Turrini, Olivier; Fernandez, Benjamin; Garnier, Jonathan; Lapuyade, Bruno; Ewald, Jacques; Adam, Jean-Philippe; Marchese, Ugo; Chiche, Laurence; Delpero, Jean-Robert; Laurent, Christophe
Abstract: Background: Sacrificing a replaced right hepatic artery (rRHA) from the superior mesenteric artery is occasionally necessary to obtain an R0 resection after pancreaticoduodenectomy (PD) for pancreatic adenocarcinoma (PA). Preoperative embolization (PEA) of the rRHA has been proposed to avoid the onset of postoperative biliary and ischemic liver complications. Methods: Eighteen patients with cephalic PA with an rRHA underwent PEA of the rRHA from 2013 to 2019. The monitoring after embolization and PD was systematic and included a clinical-biological evaluation and a computed tomography scan. This study aimed to determine the feasibility of PEA of the rRHA, postoperative morbidity at 90 days, and quality of oncologic resection after PD. Results: Feasibility of PEA was 100% without complications. A PD was performed in 16/18 patients. Mortality was 2/16 with one death after septic shock with hepatic ischemia without an arterial obstruction. Overall morbidity was 44% including one hepatic abscess after hepatic ischemia (6%). Two resections were R1 (<1 mm) in contact with the origin of the rRHA (2/4 R1). Conclusion: PEA of the rRHA before PD was safe and reproducible. PEA of the rRHA followed by en bloc PD resection seems to limit the risk of bilio-hepatic ischemia and could facilitate oncologic resection. Graphical abstract: Image 1